2021
DOI: 10.32744/pse.2021.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Research on the relationship of students' emotional and personal well-being with intelligence indicators

Abstract: Introduction. The current socio-economic situation is characterized by complexity, inconsistency, instability, which negatively affects the psycho-emotional state of citizens, reduces their level of satisfaction with life. To solve the problem of maintaining the internal balance of the individual, more and more psychological scientists are paying close attention to the study of well-being and identifying factors for its optimization. Scientists have found numerous proofs of the relationship between well-being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Participants’ demographic data, including information about gender, grade level, and major, were collected with our questionnaire. Previous research showed that those demographic variables may have a direct or mediated effect on basic Psychological needs satisfaction and emotional intelligence ( Madjar et al, 2013 ; Martin and Collie, 2019 ; Cebrian et al, 2020 ; Karapetyan, 2021 ), so they were considered as controls in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants’ demographic data, including information about gender, grade level, and major, were collected with our questionnaire. Previous research showed that those demographic variables may have a direct or mediated effect on basic Psychological needs satisfaction and emotional intelligence ( Madjar et al, 2013 ; Martin and Collie, 2019 ; Cebrian et al, 2020 ; Karapetyan, 2021 ), so they were considered as controls in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…In the current study, EI is conceptualized from the ability model developed by Mayer et al (2008) , which is defined as a mental ability for perceiving, understanding, regulating, and using one’s own and others’ emotions in thinking and action. Research literature suggests that emotionally intelligent people with higher EI also show more positive mood, higher levels of life satisfaction, well-being, flourishing, better psychological adjustment, and lower levels of psychological stress across different samples (e.g., Chu, 2010 ; Su and Reeve, 2011 ; Szczygieł and Mikolajczak, 2017 ; Mérida-López and Extremera, 2020 ; Karapetyan, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Second, participants were recruited from the western cities of China, which may limit the generalization of the findings. Compared with the eastern coastal cities, the economy of northwest China is relatively backward, and previous studies have indicated that the economic level is closely related to SWB ( Ngamaba et al, 2018 ; Ding et al, 2021 ) and EI ( Shukla and Srivastava, 2016 ; Karapetyan, 2021 ). Future studies should expand the city of the participants.…”
Section: Discussionmentioning
confidence: 99%